SUBSTITUSI BAYAM MERAH Blitum rubrum PADA FISH STICK NUGGET TERI NASI Engraulidae TERHADAP MUTU KIMIA DAN NILAI ENERGI SERTA MUTU ORGANOLEPTIK UNTUK PENCEGAHAN ANEMIA REMAJA PUTRI - HARERA ZELA WIDYASMARA; Astutik Pudjirahaju; Maryam Razak (Jurnal Pendidikan Kesehatan, 2021)
This study aims to analyze the effect of substitution of red spinach or Blitum rubrum on fish sticks of anchovies nuggets or Engraulidae on chemical quality and energy value as well as organoleptic quality for the prevention of anemia in adolescent girls. CRD 4 treatment levels with 3 times replication for each treatment level. Statistical analysis used for the content of ash, Fe and vitamin C is One Way Anova with 95 percent confidence level, data analysis for water, protein and fat content used the Calculated Value method, for carbohydrate content using the by difference method, for energy values using the Atwater method, and for organoleptic quality was Kruskal Wallis with 95 percent confidence level. The results showed that the higher the addition of red spinach, the water, Fe, and vitamin C content increased, while the ash content, protein, fat and energy values decreased. The results of the organoleptic quality assessment analysis showed that the higher the percentage of addition of red spinach, the percentage of panelists acceptance of color, aroma, and taste decreased, but the percentage of panelists acceptance of texture increased. The best treatment assessment shows that the P2 treatment level can be recommended as the best treatment level. The P2 treatment level can be used as a main animal side dish for the prevention of anemia in teenage girls.